Polymer-Based Functional Nanocomposites : Applications and Prospects. - Singh, Nakshatra Bahadur (CRC Press, 2025)
This book offers a thorough insight into polymer-based functional nanocomposites, covering their development, properties, and applications. It describes advanced processing techniques that enhance mechanical, optical, and photonic performances of these materials. Emphasizing their transformative role, it highlights cutting-edge applications in electronics, water purification, and sustainability. This book also assesses the economic viability and market potential of these materials, bridging the gap between research and real-world impact. Ultimately, it envisions how polymer nanocomposites will drive future innovations and revolutionize materials science.Key features: Provides a comprehensive overview of polymer nanocomposite fundamentals, processing techniques, and property enhancements Highlights advancements in electronics, electrical industries, and sustainability applications Examines the economic viability, industrial potential, and commercialization challenges Explores emerging innovations and the role of nanocomposites in shaping next-generation technologies This book provides a comprehensive insight into polymer-based nanocomposites, from fundamentals to industrial applications and future prospects. It is an essential resource for researchers, academics, engineers, industry professionals, innovators, and entrepreneurs.